Expression profile and function of Wnt signaling mechanisms in malignant mesothelioma cells - Fox, Simon; Richards, Alex; Kusumah, Ivonne; Perumal, Vanathi; Bolitho, Erin; Mutsaers, S.; Dharmarajan, A. (Academic Press, 2013)
Malignant mesothelioma (MM) is an uncommon and particularly aggressive cancer associated with 29asbestos exposure, which currently presents an intractable clinical challenge. Wnt signaling has been reported to play a role in the neoplastic properties of mesothelioma cells but has not been investigated in detail in this cancer. We surveyed expression of Wnts, their receptors, and other key molecules in this pathway in well established in vitro mesothelioma models in comparison with primary mesothelial cultures. We also tested the biological response of MM cell lines to exogenous Wnt and secreted regulators, as well as targeting b-catenin. We detected frequent expression of Wnt3 and Wnt5a, as well as Fzd 2, 4 and 6. The mRNA of Wnt4, Fzd3, sFRP4, APC and axin2 were downregulated in MM relative to mesothelial cells while LEF1 was overexpressed in MM. Functionally, we observed that Wnt3a stimulated MM proliferation while sFRP4 was inhibitory. Furthermore, directly targeting ß-catenin expression could sensitise MM cells to cytotoxic drugs. These results provide evidence for altered expression of a number of Wnt/Fzd signaling molecules in MM. Modulation of Wnt signaling in MM may prove a means of targeting proliferation and drug resistance in this cancer.